Evaluation of power supply capability and quality for traction power supply system considering the access of distributed generations. Issue 18 (16th February 2021) - Feng, Ding; Zhu, Hengkai; Sun, Xiaojun; Lin, Sheng
Abstract : The access of distributed generations (DGs) in the traction power supply system (TPSS) can not only make use of the renewable energy near the railway route, but also improve the condition of weak external power supply. In order to quantify the effect when DGs access TPSS, this study proposes a method for evaluating the power supply capability and quality of TPSS which considers the access of DGs. First, the method fully considers the randomness and uncertainty of the power provided by DGs and that consumed by electrical locomotives. A comprehensive model of TPSS with the access of DGs is built by means of the stochastic model, and then the index system for evaluating the power supply capability and quality of TPSS is formulated. Finally, the Monte Carlo simulation is applied to calculate the probabilistic load flow to obtain the evaluation indices. The proposed method is verified by simulating a typical TPSS in a remote mountain area. The results show that the method can quantify the power supply capability and quality of the system after the access of DGs. It can provide an intuitive conception of the power supply condition for design and operation personnel.